Influence of Mobile Learning Based on Articulatde Storyline 3 on Colloid Materials on Students' Learning Interest - Hardianti Rukmana; Das Salirawati (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to measure students' interest in learning through the use of mobile learning based on storyline 3 on colloidal material. The type of research used is experimental research. The subjects in this research were students in class XI MIPA SMA Negeri 1 Seyagen, totaling 17 students. In this research, students' interest was measured using the Pretest-Posttest technique by administering an interest questionnaire. From the results of the analysis, it is known that there was an increase of 4 students who were promoted from high to very high. The pretest and posttest results of learning interest show that learning using articulate storyline-based learning media has increased students' learning interest by 23.40%. The results of the paired t-test stated that the use of articulate storyline-based learning media was effective in increasing students' interest in learning. This research aims to measure students' interest in learning through the use of mobile learning based on storyline 3 on colloidal material. The type of research used is experimental research. The subjects in this research were students in class XI MIPA SMA Negeri 1 Seyagen, totaling 17 students. In this research, students' interest was measured using the Pretest-Posttest technique by administering an interest questionnaire. From the results of the analysis, it is known that there was an increase of 4 students who were promoted from high to very high. The pretest and posttest results of learning interest show that learning using articulate storyline-based learning media has increased students' learning interest by 23.40%. The results of the paired t-test stated that the use of articulate storyline-based learning media was effective in increasing students' interest in learning.Â